2018
DOI: 10.1038/s41598-018-28635-z
|View full text |Cite
|
Sign up to set email alerts
|

Authentication of Garcinia fruits and food supplements using DNA barcoding and NMR spectroscopy

Abstract: Garcinia L. (Clusiaceae) fruits are a rich source of (−)-hydroxycitric acid, and this has gained considerable attention as an anti-obesity agent and a popular weight loss food supplement. In this study, we assessed adulteration of morphologically similar samples of Garcinia using DNA barcoding, and used NMR to quantify the content of (−)-hydroxycitric acid and (−)-hydroxycitric acid lactone in raw herbal drugs and Garcinia food supplements. DNA barcoding revealed that mostly G. gummi-gutta (previously known as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(28 citation statements)
references
References 53 publications
0
28
0
Order By: Relevance
“…A previous report has shown that 15.5% of the total number of plant species in Thailand is used as medicinal plants (Wakdikar, 2004). Recently, a number of studies have also shown that natural health product (NHP) market samples of raw herbal trade materials are often adulterated with other species (Kool et al, 2012; Newmaster et al, 2013; de Boer et al, 2015; Kumar et al, 2015; Urumarudappa et al, 2016; Mezzasalma et al, 2017; Pawar et al, 2017; Dechbumroong et al, 2018; Raclariu et al, 2018; Liu et al, 2018; Seethapathy et al, 2018; Speranskaya et al, 2018; Tungphatthong et al, 2018; Kreuzer et al, 2019).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…A previous report has shown that 15.5% of the total number of plant species in Thailand is used as medicinal plants (Wakdikar, 2004). Recently, a number of studies have also shown that natural health product (NHP) market samples of raw herbal trade materials are often adulterated with other species (Kool et al, 2012; Newmaster et al, 2013; de Boer et al, 2015; Kumar et al, 2015; Urumarudappa et al, 2016; Mezzasalma et al, 2017; Pawar et al, 2017; Dechbumroong et al, 2018; Raclariu et al, 2018; Liu et al, 2018; Seethapathy et al, 2018; Speranskaya et al, 2018; Tungphatthong et al, 2018; Kreuzer et al, 2019).…”
Section: Methodsmentioning
confidence: 99%
“…Pawar et al (2017) used traditional DNA barcoding techniques and chemical markers to identify frequently consumed botanical dietary supplements of ginkgo, soy, valerian, yohimbe, etc. The combination of DNA barcoding and nuclear magnetic resonance (NMR) was used for the identification of admixture in Garciania species (Seethapathy et al, 2018) and Saraca acosa (Urumarudappa et al, 2016). Wang et al (2016) used DNA barcoding for the identification of processed Angelicae sinensis radix (Danggui) used in Chinese patent medicines (CPMs).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Increase in demand for phytopharmaceutical drugs in global market may lead to compromise in quality due to adulteration and substitution, which will become the greatest threat for health of consumers. [44][45][46] Availability and identification of quality phytopharmaceuticals is the major challenge for the regulatory authorities, as adulteration and mis-identification of raw material for phytopharmaceutical drug may occur due to confusion from vernacular names and inter-species variation in various geographical conditions. [46][47][48][49] Need for robust method for identification of raw material at field during collection.…”
Section: Weaknessmentioning
confidence: 99%
“…50 Moreover, herbal business generates employment opportunities to many people including farmers, local people, industry people, researchers and many more. The projected market for herbal medicines by 2023 is $ 111 billion, 51 which may became an impressive market for phytopharmaceuticals due to availability/confidence of scientific data, it can outclass the herbal and allopathic industry market. In India 90% of the herbal drug raw material are harvested from wild source and from varying geographical distribution.…”
Section: Weaknessmentioning
confidence: 99%